Actualidad en Asia (2017)
This section is carried out by the student members of the hotbed of research in Asia Pacific of EAFIT University. Within this you can find the following articles: Mega-Trade Agreements in the Pacific and the Pacific Alliance: context and perspectives, by the students Santiago Jaramillo, Juan Martín Betancur, Luisa Huertas, Mayra Alejandra Flórez, Maria Alejandra Salazar and Juan David Tobón; The growth of the middle class in China: the driving force towards democratization? made by Beatriz Vélez; Analysis of a culture reflected in the design: Naoto Fukasawa and Kenya Hara. In addition to a special Report of Asia Week 2017, Reviews of two anime: Hai to Gensou no Grimar and Fullmetal alchemist: brotherhood, a section on the Canton Fair, a special of the main news of the radio program Asia Pacific Contact and finally, a Special about the Hindi language.